2019
DOI: 10.1080/19942060.2019.1620130
|View full text |Cite
|
Sign up to set email alerts
|

Application of ANFIS and LSSVM strategies for estimating thermal conductivity enhancement of metal and metal oxide based nanofluids

Abstract: An extensive variety of chemical engineering processes include the transfer of heat energy. Since increasing the effective contact surface is known as one of the popular manners to improve the efficiency of heat transfer, the attention to the nanofluids has been attracted. Due to the difficulty and high cost of an experimental study, researchers have been attracted to fast computational methods. In this work, Adaptive neuro-fuzzy inference system and least square support vector machine algorithms have been app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 102 publications
1
43
0
Order By: Relevance
“…MLP-ANN, ANFIS, LSSVM and RBF-ANN methods were used to forecast the thermal conductivity of TiO 2 water nanofluids [45]. Similar to Razavi et al [43] study, this study also observed that LSSVM produced the best predictive results showing the least deviation factor. It is important to note that in the sensitivity analysis, the volume fraction of nanoparticles had a direct impact on the results.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…MLP-ANN, ANFIS, LSSVM and RBF-ANN methods were used to forecast the thermal conductivity of TiO 2 water nanofluids [45]. Similar to Razavi et al [43] study, this study also observed that LSSVM produced the best predictive results showing the least deviation factor. It is important to note that in the sensitivity analysis, the volume fraction of nanoparticles had a direct impact on the results.…”
Section: Introductionsupporting
confidence: 77%
“…The ANN was more accurate than the proposed correlation model, with an R 2 of 0.9997. Razavi et al [43] used particle swarm-optimised LSSVM and ANFIS to predict the thermal conductivity of nanofluids. In the study, 1109 data points were collected from experimental studies and were used to train and test the neural network.…”
Section: Introductionmentioning
confidence: 99%
“…ANN is characterized by its structure representing the pattern of connection between nodes, connection weights, and activation function. This technique has been widely used for the prediction of nanomaterial properties (Alizadeh et al, 2017;Ahmadi et al, 2019;Razavi et al, 2019). In the present study, neural network was developed using the tool box of Visual Gene Developer software (1.9).…”
Section: Prediction Modelling Using Neural Network Architecturementioning
confidence: 99%
“…In this method, the configuration have 5 different layers. The Gaussian membership function is optimized to reach most accurate answers [20][21][22][23][24]:…”
Section: Adaptive Neuro-fuzzy Inference Systemmentioning
confidence: 99%